The effect of the Dar es Salaam neurosurgery training course on self-reported neurosurgical knowledge and confidence - Waterkeyn, François; Woodfield, Julie; Massawe, Sylvia Leon; Mzimbiri, Juma Magogo; Shabhay, Zarina Ali; Bureta, Costansia Anselim; Sommer, Fabian; Mndeme, Hadija; Magawa, Dorcas Gidion; Kwelukilwa, Donatila; Ndossi, Maxigama Yesaya; Kinghomella, Alpha Ajuaye; et al. (Brain & spine, 2023)
INTRODUCTION: The Muhimbili Orthopaedic Institute in collaboration with Weill Cornell Medicine organises an annual neurosurgery training course in Dar es Salaam, Tanzania. The course teaches theory and practical skills in neurotrauma, neurosurgery, and neurointensive care to attendees from across Tanzania and East Africa. This is the only neurosurgical course in Tanzania, where there are few neurosurgeons and limited access to neurosurgical care and equipment. RESEARCH QUESTION: To investigate the change in self-reported knowledge and confidence in neurosurgical topics amongst the 2022 course attendees. MATERIAL AND METHODS: Course participants completed pre and post course questionnaires about their background and self-rated their knowledge and confidence in neurosurgical topics on a five point scale from one (poor) to five (excellent). Responses after the course were compared with those before the course. RESULTS: Four hundred and seventy participants registered for the course, of whom 395(84%) practiced in Tanzania. Experience ranged from students and newly qualified professionals to nurses with more than 10 years of experience and specialist doctors. Both doctors and nurses reported improved knowledge and confidence across all neurosurgical topics following the course. Topics with lower self-ratings prior to the course showed greater improvement. These included neurovascular, neuro-oncology, and minimally invasive spine surgery topics. Suggestions for improvement were mostly related to logistics and course delivery rather than content. DISCUSSION AND CONCLUSION: The course reached a wide range of health care professionals in the region and improved neurosurgical knowledge, which should benefit patient care in this underserved region.
Keywords: East Africa; Traumatic brain injury; Traumatic spinal cord injury; Neurosurgery; Tanzania; Education